Influence of loading condition and anatomical location on human cortical bone linear micro-cracks. (6th March 2019) - Gauthier, Rémy; Langer, Max; Follet, Hélène; Olivier, Cécile; Gouttenoire, Pierre-Jean; Helfen, Lukas; Rongiéras, Frédéric; Mitton, David; Peyrin, Françoise
Abstract: Human cortical bone fracture toughness depends on the anatomical locations under quasi-static loading. Recent results also showed that under fall-like loading, cortical bone fracture toughness is similar at different anatomical locations in the same donor. While cortical bone toughening mechanisms are known to be dependent on the tissue architecture under quasi-static loading, the fracture mechanisms during a fall are less studied. In the current study, the structural parameters of eight paired femoral diaphyses, femoral necks and radial diaphyses were mechanically tested under quasi-static and fall-like loading conditions (female donors, 70 ± 14 y.o., [50–91 y.o.]). Synchrotron radiation micro-CT imaging was used to quantify the amount of micro-cracks formed during loading. The volume fraction of these micro-cracks was significantly higher within the specimens loaded under a quasi-static condition than under a loading representative of a fall. Under fall-like loading, there was no difference in crack volume fraction between the different paired anatomical locations. This result shows that the micro-cracking toughening mechanism depends both on the anatomical location and on the loading condition.